Lenders' Use of Accounting Information in the Oil and Gas Industry. - Chung, Kwang-Hyun; Ghicas, Dimitrios; Pastena, Victor (The Accounting Review, 1993)
Abstract A borrowing base is a line of credit set by the lender and secured by petroleum assets. Borrowers can draw on the borrowing base only to the extent that their investment opportunities justify the related interest expenses. This measure of the firm's capacity to obtain secured loans is footnoted in the long-term debt section of the annual reports. In this paper we examine how lenders use accounting information to set the borrowing base of oil and gas firms. Determination of the borrowing base is a vital decision because it represents the lenders' exposure in the event that the borrower defaults. We find evidence on lenders' use of accounting information by examining actual lending agreements as well as through tests of association. Our sample consists of smaller petroleum firms that have a higher probability of default if unfavorable contingencies occur. The primary finding is that the value of firm's oil and gas reserves explain a large proportion of the variation in the firms' borrowing base and total outstanding debt. Unlike prior studies, we find that reserve recognition accounting (RRA) has a higher explanatory power than book values. Although major fluctuations in oil prices during the period of the study, 1984-1987, suggest that historical costs may be relatively poor indicators of changes in asset values, we observe that RRA information is used in setting the borrowing base for 21 of the 23 firms for which such agreements were available. The evidence reported in this article complements prior research (Harris and Ohison 1987, 1990; Ghicas and Pastena 1989) and enhances the regulators' implication that their mandated RRA information is useful to users of financial statements.